Pedagogical Approaches for Teaching Education for Sustainable Development in the Technology Education Curriculum - Blose, Princess (Research in Social Sciences and Technology, 2025)
This study investigates pedagogical strategies to teach sustainable development within the Technology curriculum in South African secondary schools, with an emphasis on the Senior Phase. Despite the global acknowledgment of sustainable development as a critical topic, its practical application in the South African Curriculum Assessment Policy Statement (CAPS) is limited. This study seeks to fill this gap by studying the pedagogical tactics used by Technology teachers to build sustainability skills. Eight technology teachers from the Ehlanzeni region in Mpumalanga Province were carefully chosen to participate. Data was collected through observations and interviews, and analysed using content analysis. The findings show that while teachers are aware of sustainable development concepts, converting this understanding into successful classroom implementation presents substantial hurdles. The study identifies teacher collaboration as the primary instrument for incorporating sustainable development principles into the technology curriculum; nevertheless, practical implementation was challenging. This study responds to the requirement of integrating sustainable development into all South African disciplines, notably the Technology curriculum It emphasises the importance of specific interventions to bridge the gap between policy intent and classroom practice.